The Impact of Education Financing on Teacher Performance in Madrasa Tsnawiyah - Eva S; Jamal Fakhri; Septuri Septuri (Universitas Negeri Semarang, 2023)
Education as a production process that produces successful graduates can be determined by the number of applicants and input components in an education system (Yohana et al, 2017). Prasejo (2010) said that education costs are a very important instrument input component in the implementation of education (in schools). There is almost no educational effort that can ignore the role of cost, so it can be said that without the cost of the education process, schools will not run. Research conducted by Sudarmono et al. (2021) revealed that education funding must refer to the standard education unit costs that have been set by a Ministerial Regulation based on the proposal of the National Education Standards Agency (BSNP). This education financing standard is expected to be used as a reference in the implementation of education at every level of education. Financing standards are standards governing the components and operating costs of educational units that are valid for one year. Financing standards include educational unit investment costs, personal costs, and educational unit operating costs (Mesiono Haidir, 2020).